Corporate Spheres of Responsibility: Architects, Cowboys, and Eco-Warriors in Myanmar's Oil & Gas Industry - Strasser, Hillary (Forest and Society, 2017)
Myanmar's recently opened economy is flush with incoming investment and activity. World leaders advocate that all businesses entering the country must operate in a "socially responsible manner." However, the history of corporate social responsibility (CSR) in Myanmar is undefined, contradictory, and complex. Thus, to get a handle around what it means to be “responsible,” this paper investigates the collective way in which actors in the petroleum industry in Myanmar enact CSR from 1990 to 2014. The oil and gas (O&G) industry is the most lucrative, and arguably powerful, national sector. The practice and philosophy of CSR, which originated in this industry, is now proclaimed to be the starting point for this newly charted course of responsible business in Myanmar. Yet, activists and critics maintain that CSR is an insincere PR measure of profit maximization whereby companies can conduct business as normal. I argue that CSR in the Myanmar petroleum industry is influenced by more complex factors than profit maximization or image management. CSR initiatives are sculpted by (1) the geography of petroleum extraction, (2) corporate philosophies and company national origins, and (3) type of company operations. The petroleum industry’s CSR activities to date, in terms of geographic span and development targets, all fit into a spectrum of assumed spheres of corporate responsibility that have been forged by the corporate ‘architects’ and tempered by geographic and global forces.